Transplacental transfer of plasticizers and flame retardants in fin whales (Balaenoptera physalus) from the North Atlantic Ocean - Sala, Berta; Garcia-Garin, Odei; Borrell, Asunción; Aguilar, Alex; Víkingsson, Gísli A.; Eljarrat, Ethel (CSIC - Instituto de Diagnóstico Ambiental y Estudios del Agua (IDAEA), 2022)
2as Jornadas de Contaminación por Plásticos (PLASTIC’2022), 21-22 de noviembre del 2022, Barcelona Marine mammals are one of the groups of animals most affected by marine pollution including that by organic compounds which, besides bearing recognised harmful effects to adults, they may also affect foetuses through placental transfer. In this study we analysed samples of fin whale (Balaenoptera physalus) females and their foetuses collected in the western Iceland summer feeding grounds in 2018. Three different families of organic pollutants: organophosphate esters (OPEs); halogenated flame retardants (HFRs); and short chain chlorinated paraffins (SCCPs), were analysed and their placental transfer investigated. HFRs were detected in 87.5% of females and 100% of foetus samples with concentrations that ranged between nd-15.4 and 6.37–101 ng/g lipid weight (lw), respectively. OPEs were detected in all samples, both from females (85.8–567 ng/g lw) and foetuses (nq-1130 ng/g lw). SCCPs were detected in 87.5% of female samples and 100% of foetal samples with concentrations that ranged between nd-30.9 and nq-574 ng/g lw, respectively. For OPE compounds, a significant negative correlation was observed between the logarithm maternal transfer ratio and their log Kow, indicating that a high lipophilicity reduced placental transfer rate. Interestingly, the decabromodiphenyl ethane (DBDPE) was the compound with the highest log Kow but also the one that was transferred the most from mothers to foetuses, calling for in-depth research on this pollutant. These results constitute the first evidence of mother-calf transfer of plasticizers and flame retardants in fin whales. Further investigations are needed to determine their potential effects on this species and other groups of animals This study was supported by the Spanish Ministry of Science and innovation (grant CEX 2018-000794-S and project PID2020-119712GBI00) (MCIN/AEI/10.13039/501100011033), by the Ministry of Economic Affairs and Digital Transformation (project ...